The Relationship between Parental Tutoring and Social Science Learning Outcomes for Fourth-Grade Students of Elementary School - Abas, Muhamad; Uge, Sarnely; Alwy, Auliya Rahmasari (Mimbar Sekolah Dasar, 2023)
Social science learning outcomes of students in elementary schools are a problem faced by teachers. Parental guidance at home is one of the influencing factors. The purpose of this study is to determine the relationship between parental tutoring and social studies learning outcomes of fourth-grade students of one public elementary school in Kendari, Southeast Sulawesi, Indonesia The research method used was ex-post facto involving total sample of 32 students, with 14 male and 18 female students. Data collection techniques were carried out using a questionnaire sheet for parental tutoring and documentation. The results show that: (1) parental tutoring for fourth-grade students was included in the very good category (59.38%, and in the good category(40.63%); and (2) there was a significant and positive relationship between parental tutoring and social studies learning outcomes. In other words, the better the parental guidance result in better children’s learning outcomes.